Holiday collector's set, volume two (DVD) Disc 1 - Trikonis, Gus; Helmond, Katherine; Caesar, Sid, 1922-; Joyner, Kimble; Hart, Melissa Joan, 1976-; Carlson, Lillian; Mackay, Don; Cooper, Frances; Camroux, Ken.; Storey, Howard; Hughes, Bob; Sullivan, Ian.; et al. ([United States] : Echo Bridge Home Entertainment, 2011)
Christmas snow: despite being evicted on the day before Christmas by their mean-spirited landlord, Mrs. Mutterrance and her children come to his aid during a blizzard.
Holiday to remember: in need of a fresh start, Caroline heads to her quaint hometown just in time for Christmas. But when she reunites with her ex-flame, they return to their old, bickering ways.
Beyond tomorrow: on Christmas Eve, three rich, self-involved businessmen die in a plane crash. As ghosts, they must make things right between two lovers on earth to earn a ticket to heaven.
Scrooge: the classic story of a miserable miser and the joy he rediscovers about the holidays.
Christmas visitor: Christmas is approaching, but George and Carol have lost the desire to celebrate since the death of their son. This year, George is determined to bring his family back together.
Angel in the family: Sisters, separated by a lifetime of misunderstanding, find themselves brought back together for one amazing Christmas.
Disc 1. Christmas snow (48 min.)(widescreen)(1986) -- Holiday to remember (90 min.)(fullscreen)(1995) -- Beyond tomorrow (84 min.)(widescreen)(1940) -- Scrooge (61 min.)(fullscreen)(1935) -- -- Christmas visitor (87 min.)(fullscreen)(2002) -- Disc 2. Angel in the family (88 min.)(widescreen)(2004).
Title from container.
"6 movie pack ; Bonus: 10 holiday songs"--Container spine.
Christmas Snow: based on the novella London snow / by Paul Theroux. A holiday to remember: based on the novel "A Christmas love" by Kathleen Creighton. Scrooge: based on A Christmas carol by Charles Dickens.
Bonus: Angel in the family DVD includes MP3 files (bonus digital audio: The Christmas Angels) of holiday songs that can be transferred to most computer and portable media players capable of playing MP3s.
Christmas snow: director, Gus Trikonis ; producer, Robert Huddleston.
Holiday to remember: director, Jud Taylor ; producers, Marilyn Stonehouse and Jud Taylor ; editor, Ron Wisman.
Keywords: Holidays -- Drama; Christmas films; Fiction films; Feature films